Anterior rectus sheath blocks in children with abdominal wall pain due to anterior cutaneous nerve entrapment syndrome: a prospective case series of 85 children. Issue 5 (10th March 2017) - Siawash, Murid; Mol, Frederique; Tjon‐A‐Ten, Walther; Perquin, Christel; van Eerten, Percy; van Heurn, Ernst; Roumen, Rudi; Scheltinga, Marc
Abstract: Background: Chronic abdominal pain in children may be caused by the anterior cutaneous nerve entrapment syndrome. Local nerve blocks are recommended as an initial treatment in adults. Evidence on effectiveness and safety of such a treatment in children is lacking. Aim: Our aim was to study outcome and adverse events of anterior rectus sheath blocks in childhood anterior cutaneous nerve entrapment syndrome. Methods: Patients <18 years of age receiving anterior rectus sheath blocks were prospectively followed. Injections were administered using a free‐hand technique in the outpatient department. Results: A total of 85 children were included (median age 15 years, range 8–17, 76% female). Eighty‐three children reported immediate pain relief following a single lidocaine block and 13 achieved long‐term success. Another 19 children was successfully treated with additional blocks combined with steroids. A total 38% success ratio was attained after a median 17‐month follow‐up (range, 4–39). Pain intensity and diagnostic delay were not associated with a beneficial outcome. However, young age predicted success. An infrequently occurring adverse event was temporarily increased pain some 6 h post injection. Conclusion: Anterior rectus sheath blocks using local anesthetics and steroids are safe and long‐term successful in more than one‐third of children suffering from abdominal pain due to anterior cutaneous nerve entrapment syndrome. Abstract :